1992
DOI: 10.1136/jnnp.55.12.1221-a
|View full text |Cite
|
Sign up to set email alerts
|

Iron and akathisia.

Abstract: B. i_ Figure A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Akathisia associated with the use of serotonin re-uptake inhibitors may be prevented or reduced with the concomitant treatment with alprazolam.26 Antiserotoninergic drugs may also be useful in the treatment of akathisia. In an open clinical trial, Weiss et a127 have shown that cyproheptadine given in a dose of 16 mg/day over four days was effective in all 17 patients treated for neurolepticinduced akathisia. Lithium-induced akathisia was claimed to be particularly responsive to mianserin.28 Although low serum iron is commonly associated with neurolepticinduced tardive akathisia, the value of iron supplements in the patients is doubtful and may even be harmful.…”
Section: Managementmentioning
confidence: 99%
“…Akathisia associated with the use of serotonin re-uptake inhibitors may be prevented or reduced with the concomitant treatment with alprazolam.26 Antiserotoninergic drugs may also be useful in the treatment of akathisia. In an open clinical trial, Weiss et a127 have shown that cyproheptadine given in a dose of 16 mg/day over four days was effective in all 17 patients treated for neurolepticinduced akathisia. Lithium-induced akathisia was claimed to be particularly responsive to mianserin.28 Although low serum iron is commonly associated with neurolepticinduced tardive akathisia, the value of iron supplements in the patients is doubtful and may even be harmful.…”
Section: Managementmentioning
confidence: 99%